A right breast gangrene: A rare breast disease - Gurwani, Siddhart; Patel, Akhilesh Kumar; Gujar, Sunil; Shinde, Siddharth; Ninama, Sneha; Gupta, Raunak Kumar; Yadav, Gaurav; Rathore, Nakul Kumar (Indian Journal of Case Reports, 2020)
Breast gangrene is a very rare disease and only a few cases have been reported in the Indian literature. Here, we present the case of a 70-year-old married female presented with complaints of pain and blackish discoloration in the right breast for 3 days. The surgery was planned on the same day with incision and drainage. Intraoperative findings were suggestive of sloughed and necrosed underlying tissue. The wound was left open and the daily dressing was planned. Then, wound closed. The patient was discharged on the 7th post-operative day. Surgeons should be aware of such ailments because breast gangrene is very rare.